TEENS, TEXT, AND TECHNOLOGY: THE PERCEPTION OF HIGH SCHOOL EFL WRITERS OF ARTIFICIAL INTELLIGENCE - Luthfia Yuha Rofiidah; Tatik Irawati (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study investigated senior high school EFL students’ perceptions of artificial intelligence (AI) in English writing activities. The study employed a qualitative descriptive design with purposive sampling involving eight EFL students in Jombang Regency who had prior experience using AI. Data were collected through open-ended questionnaires distributed via Google Forms and analyzed using thematic analysis. The results revealed two main themes: Academic Writing Support and Usability and Accessibility. Students perceived AI as beneficial for generating ideas, improving grammar, enhancing sentence clarity, organizing writing structures, increasing writing efficiency, and boosting their writing confidence. They also considered AI tools easy to learn, accessible across devices, and suitable for self-directed learning, although minor technical issues and concerns about dependence were noted. Beyond extending the constructs of perceived usefulness and ease of use from the Technology Acceptance Model, the results highlighted AI’s role as both a cognitive and emotional support system in writing. The study concluded that AI functioned not only as a technical aid but also as a reflective learning partner, shaping students’ autonomy and identity as writers. These insights suggested that AI could be integrated effectively into English language learning, provided that it is used ethically and supported by pedagogical guidance.